Mapping Indonesian Muslim Diaspora in the Netherlands - Fachri Aidulsyah; Gusnelly Gusnelly (Journal of Indonesian Social Sciences and Humanities, 2019)
Since few years ago, Indonesian government has been concerning to gain many benefits from Indonesian diaspora in various regions in the world. There are many events and agendas provided by the government which are aimed to embrace many Indonesian diaspora for giving a great contribution towards their homelands. However, its vision for gaining attention from Indonesian diaspora tends to low because the government do not have Indonesian diaspora maps in details, comprehensive, as well as described by historical trajectory. This paper aims to understand the contribution of Indonesian Muslim diaspora by mapping the role of Indonesian Muslim Organizations in the Netherlands by socio-historical perspectives. The main reasons of the Netherlands as locus of this research are; Indonesian Muslim diaspora are the first actors who promoted Islam faces in this country since 1920s and it also was acknowledged as one of the highest Muslim populated countries in Europe. Afterwards, this paper shows that there are numerous Indonesian Muslim organizations in the Netherlands from different perspectives, mazhabs, and backgrounds. Even though the government did not pillarize Indonesian Muslim organizations, albeit most of them have strong connections with some Muslim organizations in Indonesia, starting from Nahdhatul Ulama (NU) until Salafist Movement.